785. Treatment of Mycobacterium immunogenum Skin and Soft-Tissue Infections: A Case in a Peritoneal Dialysis Patient. (26th November 2018) - El-Nahal, Walid; Shenoy, Abhishek; Walker, McCall; Chopra, Tushar; Townsend, Greg; Heysell, Scott; Eby, Joshua
Abstract: Background: Mycobacterium immunogenum is a somewhat recently identified species of rapidly growing nontuberculous mycobacteria, genetically related to M. abscessus and M. chelonae . Resistance patterns of rapidly growing nontuberculous mycobacterium species can make them difficult to treat. This is particularly true of M. immunogenum, in part due to the infrequency of reported cases of human infection and limited data to guide therapy. Methods: We present here a case of M. immunogenum skin and soft-tissue infection at the site of insertion of a peritoneal dialysis catheter in a patient with end-stage renal disease. He initially presented with nodular subcutaneous lesions around his catheter site that progressed through oral antibiotics. This led to sampling which confirmed the diagnosis of M. immunogenum . We conducted a review of the literature to identify previously reported cases of M. immunogenum, including skin and soft-tissue infections, and used these data to guide management. Results: We reviewed 11 reports (cases and case series) of Mycobacterium immunogenum in the literature. Susceptibilities often take weeks to return, and so empiric therapy is based on case series, and then later adjusted based on susceptibilities. Patients received combined antimicrobial regimens with durations of 2 weeks to 12 months, with variable outcomes. Several required surgical debridement, as was the case with our patient. His PD catheter was removed and he was treated empirically with amikacin, azithromycin, and tigecycline intravenous induction. His ultimate long-term regimen was later switched to azithromycin, clofazimine, and tedizolid due to side effects and the eventually available susceptibility profile. Conclusion: The treatment of M. immunogenum remains a challenge due to the relative scarcity of data to guide treatment, and consequent lack of systemic approach to therapy. Most reported cases involve the use of a macrolide, often in combination with an aminoglycoside or a fluoroquinolone. Several started with intravenous induction, followed by transition to oral therapy on the order of weeks to months. Others also require surgical debridement. More data are required to develop a standardized approach to the treatment of M. immunogenum. Disclosures: All authors: No reported disclosures.